Occlusal vs non-occlusal modality of the loading protocol for oral implants in partially edentulous patients: a systematic review and meta-analysis - Panagiotis Kourkoutis; Rawand Shado; Ines Novo Pereira; David Madruga; Haidar Hassan (BDJ Open)
Abstract Background Occlusal loading refers to a modality in which an implant-supported prosthesis is subjected to functional loading, maintaining contact with the opposing dentition from the onset of prosthetic placement. In contrast, non-occlusal loading represents a non-functional approach, wherein a provisional implant prosthesis is initially placed in infra-occlusion or fully relieved of contact with the opposing dentition, which is subsequently (at a later stage) followed by functional (occlusal) loading with the definitive prosthesis. Aim To compare clinical outcomes in partially edentulous cases following an occlusal modality of loading versus non-occlusal modality of loading. Method A search on Pubmed, Scopus and Embase databases was conducted to identify randomised controlled trials (RCTs) comparing occlusal versus non-occlusal modalities of implant loading in partially edentulous patients receiving implants with single crowns or fixed bridges, between January 1 (2004) to June 12 (2024), examining implant survival, complications and marginal bone loss (MBL) of implants. The inclusion criteria involved RCTs of evidence level II (Oxford Centre for Evidence-Based Medicine Levels of Evidence). For assessing bias in the included studies, the Cochrane Risk of Bias tool was used. Results This review identified seven RCTs investigating 273 implants over 1–3 years follow-up periods. seven studies reported 1-year MBL data and three reported 3-year data. Publication bias was noted at the 1-year follow-up (p < 0.01) but not at 3 years (p > 0.05). Differences in MBL were not statistically significant at both 1 year (Hedges’ d = 0.01, p = 0.920, 95% CI: [−0.21, 0.24]) and 3 years (Hedges’ d = 0.01, p = 0.952, 95% CI: [−0.28, 0.30]). Differences in complication occurrences were not statistically significant (RR = 0.882, p = 0.759, 95% CI: [0.397, 1.964]). The nature of data on implant survival rates prevented a meaningful meta-analysis. Conclusion For short-term periods of 1–3 years, no significant evidence supports clinical superiority in terms of complication rates and MBL between non-occlusal and occlusal modalities of implant loading. Future studies should explore functional and aesthetic aspects, as well as patient reported outcomes to determine any short-term differences or consider long-term follow-up with large sample sizes to detect significant clinical differences.